Bold leadership is needed for transforming health care - Barilla D; Shah H; Rawson R (Dove Medical Press, 2019)
Dora Barilla,1 Huma Shah,2 Rick Rawson31Community Health Investment, Providence St. Joseph Health, Renton, WA 98057, USA; 2Loma Linda University School of Public Health, Loma Linda, CA 92354, USA; 3Administration, Adventist Health and Rideout, Marysville, CA, 95901, USAAbstract: Health care in the United States is going through significant changes and is at the forefront of the political landscape. While the health care debate rages on, leaders need to forge ahead and continue to work towards population-based health care and investing in their communities in a fiscally conscious way. Many innovations are happening but more needs to be done, especially in upstream services improving the health of the community. Research shows that investing in social care services and community-based investments results in lower health care expenditures and better health outcomes. Efforts should be placed on exploring a blended medical/social model of care while considering blended funding sources wherein the community needs to be active participants in this explorative process.Keywords: health care delivery, health system, health policy, leadership, medical and social care models